Efektivitas Self-Nanoemulsifying-Drug-Delivery-System (SNEDDS) Terhadap Bioavabilitas Obat Simvastatin : Literature Review Article - Adinda Ayesha; Annida Lutfiah; Eka Sevianti; Sahrul Setiawan; Tia Laelasari; Iin Lidia Putama Mursal (Jurnal Ilmiah Wahana Pendidikan, 2023)
Hyperlipidemia is a disease caused by increased lipid levels. Simvastatin is a medication used for the treatment of antiperlipidemic diseases, in which the medication has hard-to-solve properties in water, thereby affecting its bioavailability. Nanoemulsification drug delivery system (SNEEDS) is one of the known nanotechnology systems capable of increasing the dilution of substances that are difficult to solve in water. The aim of this study was to evaluate the self-nanoemulsifying and SNEEDS drug delivery systems on the bioavailability of non-water-soluble simvastatin. The method used is Literature Review Articles (LRA) by analyzing, identifying, and interpreting all findings into research. The results obtained from this study are the drug simvastatin using the Self-Nanoemulsifying-Drug-Delivery-System (SNEDDS) giving the result that there is an increase in the biovaibility of the drug which is aimed at the presence of the event of absorption of substances or active ingredients in the area of the intestinal tract to be much superior.